Is church attendance associated with quality of life of older adults? Findings from a cross-sectional study in Poland - Stodolska, Agata (Journal of religion, spirituality & aging, 2024)
The aim of this study was to examine if church attendance was associated with quality of life (QoL) and feeling of loneliness among older adults in Poland, and if feeling of loneliness mediated the association. Face-to-face interviews were conducted with randomly selected community-dwelling individuals aged 65+ from the general population, hospital patients, and social service users. Church attendance was positively associated with QoL regardless of confounding factors. Older adults attending church frequently felt less lonely and evaluated their health better. Feeling of loneliness mediated the association between church attendance and QoL. Religiousness should be considered as an important determinant of healthy aging.